ANALISIS PERSPEKTIF GURU SEKOLAH INDONESIA BANGKOK MENGENAI LITERASI BUDAYA DALAM FENOMENA PENCAPAIAN KETERAMPILAN HIDUP DI ABAD KE 21: Penelitian Fenomenologi Pada Mata Pelajaran PKn di Sekolah Dasar - Novia Leli Aswindya, - (2022)
Penelitian kualitatif fenomenologis dengan judul "Analisis Perspektif Guru Sekolah Indonesia Bangkok mengenai Literasi Budaya dalam Fenomena Pencapaian Keterampilan Hidup di Abad ke-21" sebagai upaya untuk mengungkap bagaimana pengalaman guru berdasarkan persepsinya dalam mengupayakan siswa yang berada di Sekolah Indonesia Luar Negeri khususnya di negara Thailand tepatnya di kota Bangkok untuk mencapai keterampilan hidup pada abad 21 yakni literasi budaya. Literasi budaya merupakan kemampuan dalam memahami dan bersikap terhadap kebudayaan Indonesia sebagai identitas bangsa. Tidaklah semudah membelajarkan kebudayaan seperti di Indonesia karena lingkungan luar sekolah SIB baik bahasa, agama, budaya, adat istiadat, lapisan sosial tentu berbeda dengan identitas yang kita miliki, begitupun dengan keterbatasan akses belajar lainnya. Desain penelitian deskriptif dengan metode fenomenologi menggunakan instrumen pengumpulan data wawancara mendalam (indepth interview) sehingga setelah dihasilkan data penelitian berupa transkrip wawancara dapat dianalisis kepada Interpretative Phenomenological Analysis (IPA) diantaranya 1) Reading and re-reading; 2) Initial noting; 3) Developing Emergent themes; 4) Searching for connections across emergent themes; 5) Moving the next cases; and 6) Looking for patterns across cases. Penelitian fenomenologi ini menguak pencapaian keterampilan abad ke-21 yakni literasi budaya di SIB terlaksana sebagaimana mestinya dengan beragam kegiatan dan dukungan diatas keterbatasan kondisi sekolah yang berada didalam kebudayaan negara lain. ------- Phenomenological qualitative research with the title "Perspective Analysis of Bangkok Indonesian School Teachers on Cultural Literacy in the Phenomenon of Achieving Life Skills in the 21st Century" as an effort to reveal how the experience of teachers based on their perspective in seeking students who are in Indonesian Schools Abroad, especially in Thailand Country at Bangkok City to achieve life skills in the 21st century, namely cultural literacy. Cultural literacy is the ability to understand and behave towards Indonesian culture as a national identity. It is not as easy to teach culture as in Indonesia because the environment outside the SIB school, whether language, religion, culture, customs, social strata, is certainly different from the identity we have, as well as other limited access to learning. Descriptive research design with phenomenological methods uses in-depth interview data collection instruments so that after the research data is produced in the form of interview transcripts, it can be analyzed for Interpretative Phenomenological Analysis (IPA), including 1) Reading and re-reading; 2) Initial notes; 3) Developing Emergent themes; 4) Searching for connections across emergent themes; 5) Moving the next case; and 6) Looking for patterns across cases. This phenomenological research reveals the achievement of 21st century skills, namely cultural literacy at SIB is carried out properly with a variety of activities and support above the limitations of school conditions that are in the culture of other countries.